The Effect of Mathematics Realistic Education Aided by Mathematics Software towards the Process of Solving Mathematical Communication Problems of Junior High School Students - Marwan Marpaung; Ani Minarni; Togi Panjaitan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
One factor that has a big influence on mathematics learning outcomes and how students provide solutions to mathematical problems, among others, is the learning factor as well as initial mathematical knowledge (IMK). So, the objectives of the research are to find out: (1) the influence of the Realistic Mathematics Education (RME) Approach aided by Microsoft Mathematics software on students' mathematical communication ability (MCA), (2) an interaction between IMK and RME approach to mathematical communication ability, (3) the students' completion process in solving mathematical communication problems. The third objective is very important because it can reveal whether horizontal and vertical mathematization as the ideas of RME benefit the students. The results of the research show that: (1) there is a significant effect of the RME Approach aided by  Mathematics software on students' mathematical communication ability, (2) there is no significant interaction between the initial mathematical knowledge and the learning approach to students' mathematical communication ability, (3) the students' completion process in solving  mathematical communication problems attain the "good" category.